Examining the Within-Individual Effect of Delinquency on Psychosocial Maturity in Mid-adolescence - Doherty, Elaine Eggleston (Journal of developmental and life-course criminology, 2021)
Extant literature examining the impact of psychosocial maturity on offending finds that diminished psychosocial maturity is related to increases in offending in adolescence, and gains in psychosocial maturity are related to desistance from offending in adulthood. Yet, we know less about the reverse of this relationship—the effect of offending on psychosocial development. To fill this gap, this study examines how within-individual changes in offending relate to within-individual changes in psychosocial maturity among a school-based sample of middle adolescents. Using 3-year panel data from a sample of 2,619 7th and 8th graders from a Midwestern county, we estimate a series of fixed-effect regression models to examine the within-individual effect of delinquency on six indicators of psychosocial maturity—impulse control, anger control, future orientation, self-esteem, school orientation, and resistance to peers. Results consistently show that engaging in higher levels of delinquency during the previous 6 months is related to lower self-reported levels of psychosocial maturity. We discuss how this finding informs our theoretical understanding of psychosocial maturity’s complex relationship with offending across the life course as well as its implications for school-based programming.